Prescribing pattern of antibiotics in pediatric department of a tertiary care teaching hospital - G. K., Nalini; ., Neelamma; Kumar D. G., Prasanna; P., Deepak; G. N., Sahana; G. N., Jayashree; Anna Valder, Bhavishya Keerthi (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Prescription is an order from doctor for medicine. Rational use of medicines requires that "patients receive medications appropriate to their clinical needs, in doses that meet their own individual requirements, for an adequate period of time, and at the lowest cost to them and their community". Irrational use of medicines is a major problem worldwide. This leads to serious morbidity and mortality also leads to reduction in the quality of treatment due to antibiotic resistance. Evaluation of prescribing pattern will help in minimizing adverse drug reactions, resistance among children. Also help to know the attitude of the physicians towards prescribing. Aim of the present study was to evaluate the prescription pattern of antibiotics in paediatric inpatients of Hassan institute of Medical Sciences. Methods: A prospective study, conducted among 110 patients below the age of 18 years and being treated with antibiotics were included in our study. The results were analyzed using descriptive statistics. Results: Out of 110 patients, female (58) and male (52) are enrolled in the study from inpatient paediatrics department, majority of patients belonged to age group of 0-5 years (74%), respiratory tract infections 29 (35%) , gastrointestinal infections 26 (22%) and central nervous system in 9 (11%). Out of 227 antimicrobial agent, about 83.48% were cephalosporins, followed by ciprofloxicin (33.94%), amoxicillin (32.11%), and amikacin (6.42%). Conclusions: Cephalosporins (ceftriaxone) were most commonly used antibiotic, which covers gram positive, gram negative and anaerobic organism.